Effects of Central Bank independence and financial stability on inflation in selected African countries - Adamu Yahaya; Mohammed T. Saidu; Abdulaziz Sadi (CBN Journal of Applied Statistics, 2022)
This study examines the relationship between central bank independence (CBI), financial stability, and inflation in 14 African countries within the period 1985-2019. Initial test revealed the presence of cross-sectional dependence (CD) among the countries. Thus, the Mean Group (MG), Common Correlated Effect Mean Group (CCEMG) and Augmented Mean Group (AMG) were employed for the analysis. The CCEMG and AMG results showed a significant and negative correlation between central bank independence and inflation. On the other hand, financial stability is only significant in the MG Model. Additional results obtained using the Garriga CBI index is consistent with our main results. The study recommends greater independence of central banks from all forms of political and government influence in order to have greater chance of achieving lower inflation within the African nations.
Keywords: E31; E58; 330; Augmented mean group; central bank independence; common correlated effect mean group; financial stability; inflation; mean group